REGRESI LINIER KENAIKAN BERAT BADAN IBU SELAMA HAMIL TERHADAP BERAT BAYI LAHIR - Yanti, Linda; ., Surtiningsih (Bidan Prada: Jurnal Publikasi Kebidanan Akbid YLPP Purwokerto, 2016)
Pregnant women who are exposed to chronic energy malnutrition (KEK) and anemia have a higher probability to BBLR compared to unexposed KEK and anemia. Objective: predict birth weight in terms of maternal weight gain during pregnancy. Methods: This study uses correlation analysis with the population in this study were all maternal and newborn babies in health centers purwokerto south, Sokaraja 1, 1 twin and 1 east purwokerto Banyumas district. Samples taken at random proportionally from the clinic, the sample size in the study was calculated using linear regression formula and obtained a sample of 90 respondents. Results and Discussion: There was a significant association maternal weight gain during pregnancy with birth weight (p <0.05) means that the higher the mother's weight gain during pregnancy, the birth weight will also increase. The higher increase in maternal weight during pregnancy the weight of BB was born to be higher (r = 0.816), it terseubut is because the fetus receives nutrients such as energy / carbohydrates, protein, fat, vitamins and minerals from the mother through the placenta Conclusion: The regression equation for estimating birth weight in terms of the mother's weight gain during pregnancy is estimated birth weight = 2198 + 83 x increase in maternal weight during pregnancy. Keywords: maternal weight gain, weight baby